Complications of submucosal endoscopy. Issue 5 (October 2016) - Gonzalez, Jean-Michel; Benezech, Alban; Barthet, Marc
Abstract: Submucosal endoscopy essentially regroups peroral endoscopic esophageal myotomy (POEM) and, more recently, pyloromyotomy and tunnel tumor resections. The complication rate of POEM is between 5% and 10%. Complications include gas-related complications, mucosal tears, and bleeding, and are usually managed conservatively or with non-surgical procedures. Only one case of death has been reported. The most commonly identified risk factors for complicated procedures in POEM are short experience with the technique and sigmoid-type esophagus. The rate of gastro-esophageal reflux (GERD) is between 10% and 30% depending on the definitions, with a good clinical response to proton pump inhibitors. For the techniques other than POEM, the number of cases reported is too small to allow identification of the complications, which, in addition, probably vary depending on the organ involved. The management of gas-related complications is conservative and sometimes requiring percutaneous exsufflation (capnoperitoneum) or drainage. The endoscopic management of mucosal tears essentially involves clip placement and, in case of bleeding, the usual hemostasis techniques including stent placement. Importantly, following a rigorous and appropriate learning program is essential to minimize the risk of complications, particularly for specialists with a short experience in the technique.